Early years neurosurgical training in the era of the European Working Time Directive. (October 2013) - Kirkman, Matthew A.; Watkins, Laurence D.; Kitchen, Neil D.; Sethi, Huma
Abstract The past decade has seen significant changes to the face of neurosurgical training in the United Kingdom, driven in part by an increasing focus on patient safety and the introduction of Modernising Medical Careers and the European Working Time Directive (EWTD). Recent reforms to neurosurgical training over the past few years have resulted in creation of an 8-year 'run-through' training programme. In this programme, early years (ST1 and ST2) trainees often lack dedicated time for elective theatre lists and outpatient clinics. Further, any time spent in theatre and clinics is often with different teams. Here we describe a training model for early years trainees at the National Hospital for Neurology and Neurosurgery, who are given the responsibilities traditionally associated with a more senior trainee including dedicated weekly theatre and clinic time under the supervision of a single consultant, in addition to out of hours experience. The advantages and considerations for implementing this model are discussed, including the benefit of guidance under a single consultant in the early stages of training, along with key educational concepts necessary for understanding its utility. We feel that this is an effective model for junior neurosurgical training in the EWTD era, expediting the trainee's development of key technical and non-technical skills, with potentially significant rewards for patient, trainee and trainer. National implementation of this model should be considered.